2001
DOI: 10.1007/pl00014589
|View full text |Cite
|
Sign up to set email alerts
|

Is exon 5 of the PTEN/MMAC1 gene a prognostic marker in anaplastic glioma?

Abstract: Chromosome 10 deletions are among the most common genetic changes in highly malignant glial tumors. It has been noted that loss of heterozygosity (LOH) at 10q23 is a frequent alteration in a variety of human tumors and occurs in approximately 70% of all glioblastomas. By mapping of homozygous deletions on 10q23, a candidate tumor suppressor gene has been isolated, called PTEN for "phosphatase and tensin homolog deleted on chromosome 10" and MMAC1 for "mutated in multiple advanced cancers-1." Mutations of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Low expression of PTEN gene product was implicated in the clinicopathological stage and metastasis of various malignancies. We found that PTEN expression was negatively correlated with invasive depth, metastasis, and growth patterns of gastric carcinomas, similar to other kinds of tumors 24–31 . It was suggested that reduced expression of the PTEN protein probably regulated invasion, metastasis and growth patterns of gastric carcinoma.…”
Section: Discussionsupporting
confidence: 68%
“…Low expression of PTEN gene product was implicated in the clinicopathological stage and metastasis of various malignancies. We found that PTEN expression was negatively correlated with invasive depth, metastasis, and growth patterns of gastric carcinomas, similar to other kinds of tumors 24–31 . It was suggested that reduced expression of the PTEN protein probably regulated invasion, metastasis and growth patterns of gastric carcinoma.…”
Section: Discussionsupporting
confidence: 68%
“…Mutations in the PTEN gene are closely related to cancer-predisposing genetic diseases including Cowden's BRRS syndrome (16). PTEN mutations have been found in a variety of tumors including prostate cancer, endometrial cancer, glioma, lung cancer and liver cancer (17).…”
Section: Effects Of the Upregulation Of Pten On Proliferation And Apomentioning
confidence: 99%
“…PTEN is also a powerful inhibitor of cell motility which was found to be independent of its catalytic domain [78] and might be linked to the N-terminal tensin and auxilin homology domains. Mutant PTEN might be linked to an aggressive clinical course [68,99]. On the other hand, human and murine tumors with an activated PI3K/PTEN/Akt pathway might be exquisitely sensitive to rapamycin, a macrolid antibiotic that downregulates mTOR and potentially opens a new therapeutic window for these tumors [22,121].…”
Section: Ink4amentioning
confidence: 99%